Factors Affecting Halal Product Purchase Intention: A Study of Instant Noodle Consumption of College Study in Bandung - Nurcahyo, Agung; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abstract.Background:  Indonesia as a country with high muslim population in the world. Furthermore, Indonesia at a second position of Top fifteen world instant noodle demand in 2015. This research aims to examine relationship of factors affecting Halal product purchase intention, case on instant noodle consumption of college student muslim in Bandung. Three factors affecting purchase intention that has been tested are Halal awareness, Halal certification and personal societal perception. Methods: The data used was obtained through online survey with 108 valid respondents. Sampling technique was used purposive method. Respondent must be muslim, student college in Bandung with range age 18-years old who ever consume instant noodle. Multiple linear regression analysis was applied to determine the interrelation of different variables in purchase intention. As the requirements to use it, the data gathered was test by Classic Assumption Test before hand. Results: The Results shows that there are significant relationship between two independent variables (Halal certification and personal societal perception) toward dependent variable (purchase intention toward Halal product). Conclusion: In this research, Halal awareness has not significant relationship toward purchase intention. This study is important to the product. Keywords:  Halal awareness, Halal certification, personal societal perception, purchase intention, instant noodle